Factorial and Economic Evaluation of an Aqueous Two-Phase Partitioning Pilot Plant for Invertase Recovery From Spent Brewery Yeast - Vázquez-Villegas, Patricia; Espitia-Saloma, Edith; Torres-Acosta, Mario A.; Ruiz-Ruiz, Federico; Rito-Palomares, Marco; Aguilar, Oscar (Frontiers in Chemistry, 2018)
Aqueous two-phase systems (ATPS) have been reported as an attractive biocompatible extraction system for recovery and purification of biological products. In this work, the implementation, characterization, and optimization (operational and economic) of invertase extraction from spent brewery yeast in a semi-automatized pilot plant using ATPS is reported. Gentian violet was used as tracer for the selection of phase composition through phase entrainment minimization. Yeast suspension was chosen as a complex cell matrix model for the recovery of the industrial relevant enzyme invertase. Flow rates of phases did not have an effect, given that a bottom continuous phase is given, while load of sample and number of agitators improved the recovery of the enzyme. The best combination of factors reached a recovery of 129.35 ± 2.76% and a purification factor of 4.98 ± 1.10 in the bottom phase of a PEG-Phosphate system, also resulting in the removal of inhibitor molecules increasing invertase activity as reported by several other authors. Then, an economic analysis was performed to study the production cost of invertase analyzing only the significant parameters for production. Results indicate that the parameters being analyzed only affect the production cost per enzymatic unit, while variations in the cost per batch are not significant. Moreover, only the sample load is significant, which, combined with operational optimization results, gives the same optimal result for operation, maximizing recovery yield (15% of sample load and 1 static mixer). Overall res ults of these case studies show continuous pilot-scale ATPS as a viable and reproducible extraction/purification system for high added-value biological compounds.